2017
DOI: 10.1104/pp.17.00702
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute 8 (AGO8) Mediates the Elicitation of Direct Defenses against Herbivory

Abstract: In , specific RNA-directed RNA polymerase (RdR1) and the Dicer-like (DCL3 and DCL4) proteins are recruited during herbivore attack to mediate the regulation of defense responses. However, the identity and role(s) of Argonautes (AGOs) involved in herbivory remain unknown. Of the 11 AGOs in the genome, we silenced the expression of 10. Plants silenced in expression grew normally but were highly susceptible to herbivore attack. Larvae of grew faster when consuming inverted-repeat stable transformants (ir) plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 83 publications
0
34
0
1
Order By: Relevance
“…In brief, DNA extracted from individual transgenic plants was used for NanoString to detect the content of inserted fragments according to the designed probes. To validate the single-copy-number insertions inferred from the segregation rates, a published single-copy insertion stably transformed line, ago8 (871-8-8), was used as a positive control [ 82 ]. The following three previously characterized transgenic lines were also used in this study: myb8 (A-07-810-2) plants silenced in the expression of MYB8 gene [ 47 ]; pmt (A-03-108-3) plants silenced in the expression of putrescine N-methyltransferase, a key nicotine biosynthetic enzyme [ 51 ]; and aoc (A-07-457-1) plants silenced in the expression of AOC, a single-copy key biosynthetic enzyme in JA biosynthesis [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…In brief, DNA extracted from individual transgenic plants was used for NanoString to detect the content of inserted fragments according to the designed probes. To validate the single-copy-number insertions inferred from the segregation rates, a published single-copy insertion stably transformed line, ago8 (871-8-8), was used as a positive control [ 82 ]. The following three previously characterized transgenic lines were also used in this study: myb8 (A-07-810-2) plants silenced in the expression of MYB8 gene [ 47 ]; pmt (A-03-108-3) plants silenced in the expression of putrescine N-methyltransferase, a key nicotine biosynthetic enzyme [ 51 ]; and aoc (A-07-457-1) plants silenced in the expression of AOC, a single-copy key biosynthetic enzyme in JA biosynthesis [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Feeding by D. noxia on susceptible and resistant wheat induced similar responses in TaAGO5 regulation for susceptible plants, where a twofold induction was observed 1 h after the aphids were placed on the plants. This increased steadily and peaked at threefold induction at 48 h. Similarly, NaAGO5 was differentially regulated in N. tabacum by M. sexta larvae oral secretions (Pradhan et al, 2017). Oral secretions elicited a sixand threefold increase in NaAGO5 and 8 at 18 h. This differential regulation in response to M. sexta oral secretions was only observed for NaAGO5 and 8.…”
Section: Discussionmentioning
confidence: 82%
“…This role is similar to that observed for NaAGO8 in Nicotiana tabacum against Manduca sexta. Results from Pradhan et al (2017) suggested this holds true for NaAGO5. Knockdown of NaAGO8 directly affected phytohormone biosynthesis and the production of nicotine, diterpenoid glycosides, and phenolamides under MYB8 transcription factor regulation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The genome of N. attenuata harbors three RDRs [4446], four DCLs [47] and 11 AGOs [48]. RdR1, DCL3 and DCL4 and AGO8 were shown to contribute to N. attenuata’s herbivore resistance [44, 47, 49]. Furthermore, the context-dependent importance of AMF on N. attenuata’s growth and fitness has been shown.…”
Section: Introductionmentioning
confidence: 99%